SURVIVAL AMID VIOLENCE AS ILLUSTRATED BY KHALED HOSSEINI - Rakib Farooq Matta; Dr. Harbhajan Kaur Khanooja (International Journal of Innovations in Engineering Research and Technology, 2023)
In the midst of all the chaos in Afghanistan, Khaled Hosseini came up with his enlightening stories, which went on to become an international literary sensation. The Kite Runner was not only regarded as a captivating work of fiction for pure enjoyment, but it also served as a resource for learning every facet of the Afghan socio-cultural atmosphere. In addition to being literary treasures, Hosseini’s works serve as a source of entertainment and information for people all over the world about the ongoing Afghan tragedy. Immigrants bring their native culture with them. However, they encounter a wide range of issues; nevertheless, they must adapt to and grow in the congregational nation. Hosseini wrote about Afghanistan, which is often associated with the Soviet War and the Taliban in the minds of many people in the west. Khaled Hosseini intended to bring attention to the fact that Afghans have been able to live in quiet anonymity. The book depicts the shattered identities of the oppressed, victimized, and downtrodden with sympathy and shows a desire and fight for survival. The central theme of all of his works is the theme of broken identity and survival. Hosseini’s main characters are incredibly alone, worried, baffled, and lost. The majority of the characters experience emotional sterility and temporary loss of human goodness because of painful social interactions with a hostile environment and extremely violent and harsh domestic situations. This paper examines the author’s varied motivations for writing, focusing on his desire to highlight the positive aspects of even the most difficult situations.